Finite element simulation of castellated beam by using civilfem with ansys software - Tan, Poh Aun (2014)
Nowadays in the construction of modem buildings, it is necessary to accommodate pipes and ducts necessary services, such as air conditioning, water supply, sewerage, electricity, computer networks and telephone networks. Finite element method is the leading technique for analysing the behaviour of structures when subjected to a variety of loads. In order to minimize storey height and achieve economic requirements most of industrial building using castellated beam. Besides that, the intention of castellated beam used in the steel structure is without any additional material also will increase the beam's web depth as well as the strength of the beam. The finite element results are compared in term of load deflection curve, pure bending, shear, and lateral torsional buckling, showing a good agreement. Hence, from the results this study was conducted that finite element analysis is able to give a similar result as the analytical results. Moreover, this results presents the castellated beam results by using the ANSYS software. The objective of this study is to obtain the maximum deflection, maximum von mises strain, maximum von mises stress by Probabilistic Design System (PDS)